Countdown - Johannsen, Iris (New York. Bantam Books., 2005)
#1 New York Times bestselling author Iris Johansen sets her readers$1 (Bpulses racing once again in this relentless psychological thriller of a young woman caught in a maze of secrets and stalked by a merciless killer. The countdown begins the moment you open this riveting novel that only grows more electrifying as the pages turn, more exciting as time runs out. s